2010
DOI: 10.2308/iace.2010.25.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Instructor-Assigned and Student-Selected Groups: A View from Inside

Abstract: This paper addresses an issue that most accounting instructors face when assigning group work: does the method of forming groups affect the group experience and, if so, how? Our study provides a student characterization of group formation effects, by examining student experiences as expressed in their own words in written journals. This view from inside the groups reveals subtle group formation effects not apparent in prior studies, and enriches findings derived from quantitative questionnaire responses. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 23 publications
4
29
0
1
Order By: Relevance
“…The extra cognitive load of needing to establish whether group members might be accepting of one’s LGBTQIA identity, debating whether or not to come out, and then going through the process of coming out means that frequently switching up groups during the term may lead to significantly more stress on LGBTQIA students that could detract from their learning. While relatively little is known about improving student comfort during group work in biology active-learning classrooms, our findings are supported by other studies that have reported that college students who have choice in who they work with report more positive group-work experiences than those who do not (Mahenthiran and Rouse, 2000; Hilton and Phillips, 2010). Furthermore, helping students feel more comfortable by allowing them to choose who to work with aligns with a recent study conducted in an active-learning biology classroom that showed women were more comfortable working in a group with their friends (Eddy, Brownell, et al.…”
Section: Discussionsupporting
confidence: 85%
“…The extra cognitive load of needing to establish whether group members might be accepting of one’s LGBTQIA identity, debating whether or not to come out, and then going through the process of coming out means that frequently switching up groups during the term may lead to significantly more stress on LGBTQIA students that could detract from their learning. While relatively little is known about improving student comfort during group work in biology active-learning classrooms, our findings are supported by other studies that have reported that college students who have choice in who they work with report more positive group-work experiences than those who do not (Mahenthiran and Rouse, 2000; Hilton and Phillips, 2010). Furthermore, helping students feel more comfortable by allowing them to choose who to work with aligns with a recent study conducted in an active-learning biology classroom that showed women were more comfortable working in a group with their friends (Eddy, Brownell, et al.…”
Section: Discussionsupporting
confidence: 85%
“…This present study's findings further explain how some participating teachers used different methods to form groups: for instance, they selected group leaders and allowed those leaders to choose the remaining group members, as they believed the leaders to be the main members in the group who would control and help their group interact and create CL. These results are in line with those from extant research (Chapman et al, 2006;Hilton & Philips, 2008), which also found that when students were allowed to form groups, they usually chose their friends, whom they felt comfortable communicating with (Chapman et al, 2006;Russell, 2010).…”
Section: Discussionsupporting
confidence: 87%
“…Equipped with the knowledge of the top BME publication areas presented in Table , finance faculty members who are interested in breaking into BME research have the potential of starting fruitful conversations with other BME researchers from disciplines other than finance. This process could lead to more cross‐fertilization and sharing of ideas across disciplinary journals—a call that still has potential for fulfillment (Hilton & Phillips, ; Eisenberg, Hartel, & Stahl, ; Rubin & Dierdorff, ).…”
Section: Discussionmentioning
confidence: 99%